Effect of Breathing Relaxation Techniques on Changes in Blood Pressure among Pregnant Women with Pre-Eclampsia - Rinda Ica Ayuni; Homsiatur Rohmatin; Agustina Widayati (KHD Production, 2023)
Hypertension in pregnancy is a pregnancy complication and is one of the three highest causes of mortality and morbidity. Deep breathing relaxation therapy can increase oxygen saturation, improve oxygenation in the blood, and create a relaxed state in the body. This study aims to analyze the effect of breathing relaxation techniques on changes in blood pressure of pregnant women with preeclampsia at the Obstetrics and Gynecology Polyclinic, Tongas Hospital, Probolinggo Regency. This study used a one-group pre-post test design (pre-experimental) using a cross-sectional study approach with 30 respondents using an accidental sampling technique. Data collection includes coding, editing, and tabulating, then analyzed manually and by computer with the Paired T-Test. Based on data from 30 respondents, the majority of pregnant women's blood pressure before being given a breathing relaxation technique experienced moderate blood pressure as many as 15 respondents (50%), while the blood pressure of pregnant women after being given a breathing relaxation technique experienced mild hypertension was 0.19 respondents (63, 3 %). obtained P Value: 0.000 and a = 0.05, meaning r <a, so that H0 is rejected, and Ha is accepted, and there is an influence of the breathing relaxation technique on changes in blood pressure of pre-eclampsia pregnant women at the Obstetrics and Gynecology Polyclinic, Tongas Hospital, Probolinggo Regency. Respiratory relaxation therapy can be done independently, is relatively easy to do compared to other non-pharmacological therapies, does not take long in therapy, and can reduce the side effects of pharmacological therapy. for pregnant women with hypertension.